Development of a Project-Based Learning E-Module with a Deep Learning Approach for Elementary Science Learning - Endang Susilowati; Arif Rahman Aththibby; Dasrieny Pratiwi; Friska Octavia Rossa (Postgraduate, University of Mataram, 2026)
This study developed a Project-Based Learning (PjBL) e-module integrated with a deep learning approach for teaching the human respiratory system in elementary school. The research employed the 4D model: define, design, develop, and disseminate. At the define stage, curriculum demands, learner characteristics, concepts, and learning tasks were analyzed. The design stage aligned PjBL syntax with contextual problems, a simple lung-model project, scientific literacy activities, reflective prompts, and assessment instruments. Product quality was examined through validation by three material experts and three media experts, followed by a limited practicality test. The material experts awarded a total of 78 of 80 points (97.50%), and the media experts awarded a total of 76 of 80 points (95.00%), resulting in a mean feasibility score of 96.25%, categorized as very feasible based on the predetermined feasibility criteria. Practicality reached 91% according to three teachers and 89% according to fifteen Grade V students, with a mean score of 90%, categorized as very practical based on the predetermined practicality criteria. The findings indicate that the module is content-appropriate, visually organized, navigable, and operationally usable for limited elementary science learning. Its main contribution is the explicit pedagogical alignment among project stages, conceptual connections, evidence-based reasoning, and reflection. A controlled effectiveness study remains necessary before causal claims can be made regarding gains in problem-solving and scientific literacy.